THE IMPACT OF ROAD NETWORK DEVELOPMENT ON AGRICULTURAL AND INDUSTRIAL LAND USE IN KARAWANG REGENCY - Irnanda Satya Soerjatmodjo (University Muhammadiyah Jakarta, 2023)
The efficient flow of goods and services serves as a keystone of economic development, essential for thriving market dynamics and total commercial efficiency. Far from being a mere conduit, transportation infrastructure takes on a foundational function, spurring industrial growth and having a significant impact on local economies. The crucial part that transportation networks play in advancing trade across sectors serves as evidence of the symbiotic relationship between transportation and economic development. The goal of the research is to determine how the development of the Jakarta - Cikampek toll road has affected the land use shifting from the agricultural to industrial sectors, which has a significant impact on Karawang regency's economic growth. Then create the mathematical model that enables information about the value of the agriculture sector's GDRP (Gross Domestic Regional Product) based on the influence of the value of the industrial sector's GDRP to be served.